Cervical cancer prevention and control in women living with human immunodeficiency virus. (9th September 2021) - Castle, Philip E.; Einstein, Mark H.; Sahasrabuddhe, Vikrant V.
Abstract: Despite being highly preventable, cervical cancer is the fourth most common cancer and cause of cancer death in women globally. In low‐income countries, cervical cancer is often the leading cause of cancer‐related morbidity and mortality. Women living with human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome are at a particularly high risk of cervical cancer because of an impaired immune response to human papillomavirus, the obligate cause of virtually all cervical cancers. Globally, approximately 1 in 20 cervical cancers is attributable to HIV; in sub‐Saharan Africa, approximately 1 in 5 cervical cancers is due to HIV. Here, the authors provide a critical appraisal of the evidence to date on the impact of HIV disease on cervical cancer risk, describe key methodologic issues, and frame the key outstanding research questions, especially as they apply to ongoing global efforts for prevention and control of cervical cancer. Expanded efforts to integrate HIV care with cervical cancer prevention and control, and vice versa, could assist the global effort to eliminate cervical cancer as a public health problem.